Opi Mall Marketing Communication Efforts to Increase the Number of Visitors During the Covid-19 Pandemic in 2021 - Damai Yanti, Febby Ayu; Maharani, Dwi (Devotion : Journal of Research and Community Service, 2022)
Coronavirus disease (COVID-19) 2019 in Wuhan, China has developed into a pandemic since it was announced by WHO on March 11, 2020. Then it grew rapidly and out of control to become worldwide including in Indonesia. Judging from the case of the development of the COVID-19 rate which has decreased and the vaccination efforts carried out by the government, it has had a positive impact on micro, and macro businesses to public service facilities or malls. Considering the Mall is a public place with the most crowds. So it is necessary to re-strike the Marketing Communication to increase the number of visitors in the era of endemic. In this case, good and detailed marketing communication skills and strategies are needed to attract visitors' interest to come to OPI Mall. Marketing Communication is a communication activity that aims to convey messages to consumers through various media, with the hope that the communication delivered can produce three stages of change, namely changes in knowledge. The forms of marketing communications for OPI Mall are advertising, personal selling, sales promotion, publicity, and event marketing. The results of his research are management and marketing communication using various forms of marketing communication. To attract visitors and as the most effective form of publication. Advertising activities from OPI Mall are often carried out through social media promotions by the development of information technology at present as well as a form of increasing brand awareness of participant tenants and other public service facilities at OPI Mall.